Role of Sn in Pt-Re-Sn/Al2O3-Cl catalysts for naphtha reforming - Mazzieri, Vanina Alejandra (2005)
The influence of Sn addition on the catalytic activity of Pt-Re/Al 2O3 naphtha reforming catalysts was studied. Trimetallic Pt-Re-Sn catalysts supported on chlorided alumina were prepared by coimpregnation. The content of Re and Pt was 0.3%, while the Sn load was varied between 0.0 and 0.9% (weight basis). In order to make a comparison, Pt/Al 2O3 and Pt-Re/Al2O3 catalysts were also prepared. The acid function of the catalysts was studied by means of temperature programmed desorption of pyridine and the reaction test of n-pentane isomerization. Temperature programmed reduction and cyclohexane dehydrogenation were used to characterize the activity of the metal function. n-C7 dehydrocyclization was used as a test of the combined action of the acid and metal function. It was found that Sn decreases the amount of strong acid sites of chlorided alumina producing catalysts with lower cracking activity. In the case of the trimetallic Pt-Re-Sn catalyst, Sn addition to Pt-Re decreases the hydrogenolytic activity and increases both the isomerization activity and the stability. The best catalyst is the one with 0.1% Sn. The addition of Sn to Pt-Re catalysts also decreases the benzene/i-C7 ratio of the reformate, an important issue from an environmental point of view.